2021
DOI: 10.7883/yoken.jjid.2019.273
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Post-Tooth Extraction Complications in HIV-Infected Patients: a Retrospective Study

Abstract: To assess the rate and risk factors of postoperative complications following tooth extraction in HIV-infected patients by CD4 count. The study subjects were 231 HIV-infected patients who underwent tooth extraction at our institution between January 2007 and December 2011. Results of blood test, underlying diseases, surgical site, extraction method, and postoperative complications were obtained from the medical records. The risk factors potentially involved in postoperative complications were analyzed by multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Another study found that the relationship between HIV, CD4 count, viral load, and surgical site infection was not robust and was uncertain after sensitivity analysis in a meta-analysis of 18 cohort studies ( 8 ). Similarly, whether or not to extract teeth in HIV-positive patients was unrelated to CD4 count in 231 HIV-positive patients who underwent tooth extraction ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that the relationship between HIV, CD4 count, viral load, and surgical site infection was not robust and was uncertain after sensitivity analysis in a meta-analysis of 18 cohort studies ( 8 ). Similarly, whether or not to extract teeth in HIV-positive patients was unrelated to CD4 count in 231 HIV-positive patients who underwent tooth extraction ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…16 patients undergone tooth extraction, only showed post extraction pain that indicate delayedhealing, as a study showed that no difference is found regarding the complication rate post-minor oral surgery in HIV-positive patients(Nakagawa et al, 2021) …”
mentioning
confidence: 97%